An Integrated Strategy towards Enhanced Performance of the Lithium–Sulfur Battery and its Fading Mechanism. Issue 69 (14th November 2018) - Huang, Xia; Luo, Bin; Knibbe, Ruth; Hu, Han; Lyu, Miaoqiang; Xiao, Mu; Sun, Dan; Wang, Songcan; Wang, Lianzhou
Abstract: To fulfil the potential of Li–S batteries (LSBs) with high energy density and low cost, multiple challenges need to be addressed simultaneously. Most research in LSBs has been focused on the sulfur cathode design, although the performance is also known to be sensitive to other parameters such as binder, current collector, separator, lithium anode, and electrolyte. Here, an integrated LSB system based on the understanding of the different roles of binder, current collector, and separator is developed. By using the cross‐linked carboxymethyl cellulose–citric acid (CMC‐CA) binder, Toray carbon paper current collector, and reduced graphene oxide (rGO) coated separator, LSBs achieve a high capacity of 960 mAh g −1 after 200 cycles (2.5 mg cm −2 ) and 930 mAh g −1 after 50 cycles (5 mg cm −2 ) at 0.1 C. Moreover, the failure mechanism at a high sulfur loading with characteristics of fast capacity decay and infinite charging is discussed. This work highlights the synergistic effect of different components and the challenges towards more reliable LSBs with high sulfur loading. Abstract : Lithium–sulfur batteries : The practical application of lithium–sulfur batteries depends on systematic optimization of the complicated system. A facile integrated approach based on the synergy between the current collector, binder, and separator is developed to improve the performance of batteries. The synergistic effect of different components and the failure mechanism of batteries with high sulfur loading are discussed (see scheme).